(untitled) (Scientific journal of the Fergana State University, 2026)
In this study, the results of the study of the empirical heat of formation, semiempirical heat of formation, bond lengths, atomic charge values, IR spectra, HOMO-LUMO (2D and 3D states), and UV spectra of 1-(p-toluylazo)naphthol-2 in the Hyperchem program were presented. The theoretical data obtained in ChemOffice, Hyperchem, were compared with the results obtained in real (applied research).